The Effect of Biosaka Elicitor Types and Concentrations on the Growth and Yield of Chili Pepper (Capsicum frutescens L.) - Andrian Tri Susanto; Makhziah Makhziah; Juli Santoso (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2026)
Chili pepper (Capsicum frutescens L.) is an important horticultural crop that requires sufficient production to meet increasing market demand. This study aimed to evaluate the effects of Biosaka elicitor composition and concentration on the growth and yield of chili pepper. The experiment was arranged in a two-factor factorial Randomized Complete Block Design (RCBD) with three replications. The first factor was Biosaka composition (J), consisting of five formulations: J1 = babandotan, J2 = J1 + pukul empat, J3 = J2 + patikan kebo, J4 = J3 + meniran, and J5 = all biosaka materials. The second factor was Biosaka concentration (K), consisting of three concentration levels: K1 = 1.5 mL/L, K2 = 2.5 mL/L, and K3 = 3.5 mL/L. The results showed that Biosaka composition significantly affected plant height at 21–63 DAT, stem diameter at 28–63 DAT, leaf number at 21–63 DAT, fruit number per plant at the fifth harvest, and fruit weight per plant at the first and fifth harvests. Biosaka concentration significantly affected plant height at 21 DAT and 42–56 DAT, leaf number at 49 and 56 DAT, and fruit number (total fruit number and fruit number per plant) at the first, fourth, and fifth harvests. Overall, the J5 formulation and the concentration of 2.5 mL/L tended to produce the most favorable growth responses in chili pepper plants.